Design and Develop Forensic Application on Client Server Network - Suarnata Wahyu Putra, Putu Bayu; Dwi Suarjaya, I Made Agus; Wibawa, Kadek Suar (JITTER : Jurnal Ilmiah Teknologi dan Komputer, 2022)
Client server networks allow for creating efficiency and effectiveness in doing activity with teamwork, such as sharing resources. Improving technological development goes hand in hand with increasing crime rates caused by technology. Crimes that use technology still leave a trace that can be traced so that it can be paralleled with digital forensics. Digital forensics are usually done one by one per computer and cause it to take longer time to get evidence in criminal act. Looking at the problem, this study discusses the design of forensic applications on client server networks with live forensic methods and socket programming to perform forensics at the same time. Applications use Java sockets to establish a connection between the server and the client and the elevator method. The result of this study is server can collect data, like data of RAM, captured image, and snapshot disk from clients